Myrcia guedesiae (Myrtaceae), a new species from the Atlantic Forest of Bahia, Brazil - Melo, Janine Dias De Oliveira; Stadnik, Aline; Roque, Nádia (Phytotaxa, 2020)
Myrcia guedesiae, a new species from the Atlantic Forest of South of Bahia State, is described and illustrated. Morphologically, the new species belongs to Myrcia sect. Aulomyrcia and is apparently related to M. hirtiflora and M. racemosa, differing in its leaves, inflorescences branches, number of flowers, hypanthium and calyx lobes on fruits.